Studi geomorfologi Daerah Samaturu, Kabupaten Kolaka, Provinsi Sulawesi Tenggara - Hasrul Hasrul; Hasria Hasria; Suryawan Asfar (OPHIOLITE : Jurnal Geologi Terapan, 2020)
Administratively, the research area is in the Samaturu area, which includes three villages; Liku Village, Lawulo Village, and Puulawulo Village, which belong to Kolaka Regency, Southeast Sulawesi Province. Geographically, the study area is limited by 3˚58’30”-4˚1’00” LS and 121˚27’30”-121˚29’20” BT. The study area has a length of 5 km and a width of 5 km, with an area of 2.500 Ha. The purpose of this study was to determine the geomorphological conditions in the Samaturu area, Kolaka Regency, Southeast Sulawesi Province. The research method used is the DEMNAS image interpretation method and direct observation in the field to study and determine the geomorphological conditions in the study area. The result showed that the geomorphological conditions of the study area were divided into two units. The units observed were structural form units with the hills of fault zones and fluvial origin with alluvium landscapes. Flow patterns that develop in the study area are rectangular and concerted with young to adult geomorphological stages